Postgraduate Studies in Africa: The Looming Crisis - Tettey, Wisdom (International Higher Education, 2009)
Academic staff shortage has become a huge challenge for African universities, and no respite seems to be in sight. This article argues characteristics of African universities: postgraduate student enrollment, gender distribution, master's and doctoral enrollees and program choices, graduation, retention, and completion rates. To regenerate academe, African tertiary institutions will not only have to improve the relative numbers, proportion, distribution, and quality of postgraduate students who enter but also ensure that these same characteristics are reflected in postgraduate output.